Happiness and Suffering in the Perspective of Sufism (Tasawuf) - Khalid Al Walid; Nurul Ain Norman (Syifa al-Qulub : Jurnal Studi Psikoterapi Sufistik, 2022)
Abstract: Suffering and happiness are common conditions that occur in human lives. Man's innate nature led humans to strive for the prior and avoid the latter; however, being understood differently brought confusion and depression to people. Here we will analyse the Sufis' various perspectives on suffering, which will lay a new perspective that can transform sufferings into happiness. By adopting the descriptive analysis method and psychological approaches to Sufism, the research shows that happiness is understood as a matter of meaning or perception, and suffering allows the deepening of self-quality. This article also offers several Quranic and Sufi practices to achieve happiness. For example, maintaining piosity, consuming healthy and halal food, enduring patience, performing invocation (dhikr), prayers (salah), holy war (jihad), and job duties, as well as forbidding what is wrong and commanding what is right in a truthful way.